Menjaga Standar Kehalalan Produk Usaha Mikro Kecil dan Menengah Pasca Mendapatkan Sertifikasi Halal di Kota Metro - Fauzi, Ahmad Agus; Lutfi Nuraini; Yusniarti, Astri (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2025)
This study examines the efforts of Micro, Small, and Medium Enterprises (MSMEs) in maintaining halal product standards after obtaining halal certification in Metro City. Halal certification is a business ethic that should be carried out by producers as a halal guarantee for consumers. The number of MSMEs in Metro City is currently 19,824 spreadacross sub-districts and villages. Although MSMEs that have obtained halal certificates benefit in terms of consumer trust and market access, they often experience difficulties in maintaining halal product quality standards. This study is a qualitative study with a field research method. Data were obtained from interviews and observations with several business actors spread across Metro City as well as several sources from journal articles and related books. Based on the research that has been conducted, it was concluded that most MSMEs in Metro City have halal certification. MSME actors strive to maintain halal product standards, both before and after obtaining halal certification. Maintaining here is not only by attaching a halal label, but also maintaining the quality of the basic substances or materials and maintaining the source of how to process them into finished goods and ready to be distributed.